2020
DOI: 10.1002/lno.11552
|View full text |Cite
|
Sign up to set email alerts
|

Resolving marine dissolved organic phosphorus (DOP) composition in a coastal estuary

Abstract: A mechanistic understanding of dissolved organic phosphorus (DOP) utilization, and its role in the marine P cycle, requires knowledge of DOP molecular composition. In this study, a recently developed approach coupling electrodialysis and reverse osmosis with solution 31 P-NMR analysis was used to examine DOP composition within a tidally dominated salt-marsh estuary (North Inlet, South Carolina) over seasonal and tidal time frames. The isolation technique allowed for near complete recovery of the DOP pool (90% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Thereby, 31 P NMR spectroscopy played a crucial role to secure that the samples were not biased by the extraction method. During a followup study, seasonal and tidal changes of DOP were investigated that was extracted from the water of a salt-marsh estuary located in South Carolina with the RO/ED technique described in their previous publication (Bell et al 2020). Notably, the recovery rates of DOP in this study reached 90% ± 13%.…”
Section: Studies Using 1d Nmr Spectroscopymentioning
confidence: 86%
See 2 more Smart Citations
“…Thereby, 31 P NMR spectroscopy played a crucial role to secure that the samples were not biased by the extraction method. During a followup study, seasonal and tidal changes of DOP were investigated that was extracted from the water of a salt-marsh estuary located in South Carolina with the RO/ED technique described in their previous publication (Bell et al 2020). Notably, the recovery rates of DOP in this study reached 90% ± 13%.…”
Section: Studies Using 1d Nmr Spectroscopymentioning
confidence: 86%
“…While essentially all NMR spectroscopic studies investigating dissolved organic nitrogen used solid-state NMR spectroscopy, a few solution-state NMR studies on dissolved organic phosphorous (DOP) have already been reported Minear 1994a, b, 1997;Bell et al 2017Bell et al , 2020. Minear (1994a, b, 1997) investigated lake freshwater samples in all of their studies.…”
Section: Studies Using 1d Nmr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…61–63 In the meantime, phosphate esters, particularly monoesters, are the most significant parts of the dissolved organic phosphorus in soils and waters (including the ocean) in our contemporary Earth's environment. 64–68 Many other laboratory studies have confirmed the release of orthophosphates from a variety of phosphate esters when iron oxide is present. 69–77 However, the importance of inorganic phosphatase is underestimated from the view of biogeochemistry.…”
Section: Introductionmentioning
confidence: 93%
“…Radiolabelled adenosine 5 0 -triphosphate (ATP) was used to determine DOP uptake. Using 31 P-NMR analysis, studies have shown that phosphorus esters comprise the majority of high-molecular weight DOP in the ocean (75%) and in tidal salt marshes (phosphomonoesters: 61%, phosphodiesters: 31%) (Bell et al, 2020;Kolowith et al, 2001). Therefore ATP, a triphosphate monoester was used as a proxy for DOP uptake for both L. chondrodes and H. heliophila.…”
Section: Organic Phosphorus Uptakementioning
confidence: 99%